ADVISING SPEECH ACT IN AN INTERACTIVE STORY TELLING PERFORMED BY AN ISLAMIC KINDERGARTEN TEACHER - Nanik Retnowati (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2021)
The aim of this study is to describe the speech act of advising found in an interactive story telling event in a classroom setting. The speech act of advising is one of the sub type of directive speech act based on Searle’s classification which is different from other subtypes such as suggesting. The data on the speech act were taken first by identifying the interaction occuring as the unit of analysis, then points out the units which show advising. Finally, using the theory of speech act and politeness and considering social and cultural contexts, a description of any aspects related to the speech act of advising was proposed. This study found that advising is not performed directly in story telling. Instead, most of the utterances reflect indirect advices. Within the framework of intertextuality and the function of story telling in educational context, the writer comes to signify that a storytelling activity enables the teacher performs many kinds of advises delivered in non threatening mode. Comparative study on the effectiveness of indirect advice through story telling and direct advice should be the prospective further study.